Teachers' Perceptions of ICT-assisted Reading Skills Teaching Strategies in Elementary Schools: A Qualitative Approach - Purmadi, Ary (UNDIKMA, 2024)
This study aims to describe elementary school teachers' perceptions of ICT-assisted reading skills teaching strategies. This research uses a qualitative approach with data collection methods through semi-structured interviews and classroom observations. This research uses a qualitative approach. A qualitative approach was chosen because this research aims to understand and describe teachers' perceptions of reading skills teaching strategies in depth and contextually. The research results show that teachers have a positive perception of the importance of teaching reading skills. Teachers use various strategies for teaching reading skills, such as extensive reading, intensive reading, and metacognitive strategies. However, teachers still face several challenges in implementing reading skills teaching strategies, such as limited time, lack of learning resources, and differences in student abilities.